Potential Use of Kepok Banana Peel Waste as Raw Material for Carboxymethyl Cellulose for Oil and Gas Drilling Fluid Applications - Wastu, Apriandi Rizkina Rangga; Permadi , Asep Kurnia; Wahyuningrum, Deana; Nugrahanti, Asri (Scientific Contributions Oil and Gas, 2026)
This research aims to evaluate the potential of kepok banana peel as a raw material for carboxymethyl cellulose synthesis and to assess its effects on the rheological properties and filtration of bentonite-based drilling mud. CMC is synthesized through a process of delignification, bleaching, alkalization, and carboxymethylation. CMC characterization includes alpha cellulose content, degree of substitution, purity, pH, FTIR, SEM, and EDS. The obtained CMC was added in drilling mud at concentrations of 3 g, 6 g, and 9 g, and the resulting mud was tested for mud rheology and filtrate volume. The results showed that the alpha-cellulose content was 91.60%, the degree of substitution was 1.0, and the purity was 88.17%, meeting the SNI CMC grade II standard. The application of CMC increased plastic viscosity (12–14 cP), yield point (19–21 lb/100 ft²), and gel strength (8–13 lb/100 ft² for 10 seconds; 12–17 lb/100 ft² for 10 minutes) as the concentration increased. The filtrate volume decreased from 15 ml to 13 ml/30 minutes, and the mud cake thickness decreased from 0.5 mm to 0.3 mm. The pH value was stable in the range of 9. It was concluded that CMC derived from kepok banana peel has the potential to serve as an environmentally friendly drilling mud additive.